(untitled) (Research, Society and Development, 2023)
Introduction: The competence to evaluate is essential in any profession in the health area. The concept of comfort is intrinsically linked to palliative care, being a concern shared by any health professional. These, when analyzing, must know what they are looking for and what they should expect to find. Objectives: To map how health professionals assess people’s comfort in palliative and end-of-life situations. Methods: will follow the methodology proposed by the Johanna Briggs Institute (JBI) for scoping reviews. Considered studies in Spanish, English and Portuguese, without temporal definition. Databases to search: MEDLINE Complete, Academic Search Complete, CINAHL Complete and Mediclatina (EBSCOhost), Scopus and Web of Science Core Collection. For unpublished studies, the RCAAP (open access repository in Portugal) will be used. Two independent reviewers will evaluate the articles and extract the data using a specific tool created. In case of discrepancies, a third reviewer will be requested. Results: It is expected to map the data used by health professionals in assessing the comfort of people in palliative care. Conclusions: This review will make it possible to identify instruments used to collect data and what is the professional competence of the group that has in its practice the assessment of comfort. This can form the basis for a systematic review and/or help identify gaps where it may be important to invest in the future. This protocol was registered on the OSF platform with the DOI: 10.17605/OSF.IO/UF52X.